2002
DOI: 10.1073/pnas.022056399
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Xenopus oocyte meiotic maturation by catalytically inactive protein kinase A

Abstract: Progesterone induces G2-arrested Xenopus oocytes to develop into fertilizable eggs in a process called meiotic maturation. Protein kinase A (PKA), the cAMP-dependent protein kinase, has long been known to be a potent inhibitor of meiotic maturation, but little information is available on how PKA functions. We have cloned two Xenopus PKA catalytic subunit isoforms, XPKA␣ and XPKA␤. These proteins are 89% identical and both inhibit progesteroneinduced meiotic maturation when overexpressed at low levels, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 44 publications
7
66
0
Order By: Relevance
“…More recently, it has been found that injection of catalytically inactive PKA can also block progesterone-and Mosinduced GVBD and partially reduces cyclin B-induced GVBD. By contrast, inactive PKA is completely unable to block Cdc25-induced GVBD (Daar et al, 1993;Matten et al, 1994;Schmitt and Nebreda, 2002). Our results, combined with the observation that the kinase activity of PKA is required for inhibiting activation of cyclin B/Cdc2 by Cdc25, suggest that in addition to Cdc25 in Xenopus oocytes (Duckworth et al, 2002) and Wee1B in mouse oocytes (Han et al, 2005), serine 321 of Cdc25B is a potential target site for PKA phosphorylation in mouse oocytes.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…More recently, it has been found that injection of catalytically inactive PKA can also block progesterone-and Mosinduced GVBD and partially reduces cyclin B-induced GVBD. By contrast, inactive PKA is completely unable to block Cdc25-induced GVBD (Daar et al, 1993;Matten et al, 1994;Schmitt and Nebreda, 2002). Our results, combined with the observation that the kinase activity of PKA is required for inhibiting activation of cyclin B/Cdc2 by Cdc25, suggest that in addition to Cdc25 in Xenopus oocytes (Duckworth et al, 2002) and Wee1B in mouse oocytes (Han et al, 2005), serine 321 of Cdc25B is a potential target site for PKA phosphorylation in mouse oocytes.…”
Section: Discussionmentioning
confidence: 63%
“…The role of the cAMP/PKA signaling pathway in meiotic resumption of oocytes has been observed in numerous reports. High PKA activity suppresses Mos accumulation and inhibits the ability of injected Mos, cyclinB or Cdc25 to induce GVBD, suggesting that PKA inhibits oocyte maturation at several steps (Daar et al, 1993;Schmitt and Nebreda, 2002). More recently, it has been found that injection of catalytically inactive PKA can also block progesterone-and Mosinduced GVBD and partially reduces cyclin B-induced GVBD.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that PKA activity is required to maintain oocytes of all species tested in their natural G 2 arrest and that a drop in PKA activity is required for the G 2 /meiosis I transition (O'Connor and Smith, 1976;Maller and Krebs, 1977;Speaker and Butcher, 1977;Maller et al, 1979;Mulner et al, 1979;Finidori-Lepicard et al, 1981;Huchon et al, 1981;Sadler and Maller, 1981;Masui, 1985). Phosphorylation of cdc25C Ser287 by PKA has recently been shown to be required to maintain the G 2 arrest (Duckworth et al, 2002;Schmitt and Nebreda, 2002). In the early embryonic cell cycles, PKA activity has been reported to oscillate, being high in mitosis and low in interphase, and high PKA activity blocks entry into mitosis (Grieco et al, 1994(Grieco et al, , 1996.…”
Section: Wee1 and Cdc25 Phosphorylationmentioning
confidence: 99%
“…C-TAK1, identified as a human Ser216 phosphorylating activity from mammalian somatic cells, was the first to be described (Ogg et al, 1994;Peng et al, 1998). Protein kinase A (PKA), a well-known inhibitor of the G 2 /meiosis I transition, helps to maintain Xenopus oocytes in their natural G 2 arrest through phosphorylation of cdc25C on Ser287 (Duckworth et al, 2002;Schmitt and Nebreda, 2002). In fertilized Xenopus eggs, calmodulin-dependent protein kinase II (CaMKII) seems to be responsible for the majority of Ser287 phosphorylation during interphase of the first mitotic cell cycle (Hutchins et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During prophase arrest in oocytes, cyclin B-CDK1 remains inactive due to the maintenance of high levels of cAMP within the oocyte and the subsequent sustained activation of protein kinase A (PKA; Figure 3; Mehlmann et al, 2002;Schmitt and Nebreda, 2002). PKA phosphorylates and inactivates the Cdc25 isoform Cdc25B which is responsible for cyclin B-CDK1 activation in oocytes (Lincoln et al, 2002;Pirino et al, 2009;Oh et al, 2010).…”
Section: Prophase Arrestmentioning
confidence: 99%